EVALUASI SISTEM PEMBUMIAN PADA INSTALASI LISTRIK RUMAH TANGGA DI LEMBANG POTON TANA TORAJA - Ariyen Duri'; Martina Pineng (Bajang Institute, 2026)
The grounding system is a crucial component of electrical installations, serving to protect humans and equipment from electric shock, fire, and damage caused by electrical disturbances. In rural areas with mountainous soil, grounding systems often do not meet safety standards. This study aimed to evaluate the performance of residential grounding systems in Lembang Poton, Bonggakaradeng District, Tana Toraja Regency. A field experiment was conducted by measuring grounding resistance using an earth tester at several rod electrode depths. Soil treatments were applied, including natural conditions, water addition, and a water–salt mixture, to assess their effects on grounding resistance. Data were analyzed descriptively and compared with the 2011 PUIL standard. Results indicated that grounding resistance decreased as electrode depth increased. Water and water–salt treatments significantly reduced grounding resistance, with the lowest values observed in the water–salt condition. However, the measured resistance still exceeded the maximum 5 Ω limit set by PUIL 2011. These findings provide insight into the actual performance of grounding systems in mountainous areas and serve as a basis for technical recommendations to enhance the safety and effectiveness of residential electrical installations.